Developing Well-informed, Critically Thinking, and Active Citizens Through the Connection of Modeling & Simulation and Social Studies Education. Issue 1 (4th March 2019) - Hartshorne, Richard; Waring, Scott M.; Okraski, Hank
Abstract: While the importance of Science, Technology, Engineering, and Mathematics (STEM) education to address complex world problems, such as global warming, disease, and an increasingly interdependent world economy has led to many educational reform efforts in recent years, other content areas, such as social studies, have unnecessarily become marginalized. As STEM is not a standalone subject area, it serves as a tool to facilitate the learning of a variety of topics and is best served when integrated into all content areas, establishing a collaborative, rather than competitive, culture of content throughout the academic environment. To date, though, this integrated culture has not been realized.